Between Productive Specialization and Agroecology:: The Social Reproduction Strategies of Family Farmers from the Far West Region of Santa Catarina, Brazil - Capellesso, Adinor José; Cazella, Ademir Antonio (Sustainability in Debate, 2015)
This article analyzes the social reproduction strategies of family farmers with the purpose of assessing their ways of insertion in the market and the possible environmental implications of this insertion. A total of 37 interviews with conventional and organic production family farmers from the Far West Region of Santa Catarina were conducted. While integrated swine and aviculture production generates specialization, agroecology seeks productive diversification. Between these poles, dairy farming has a high level of social expression, but is recently reshaping its relation with the markets. The demand for scale is necessary to remain the market chain and get better prices. In consequence, local family farmers are expanding a high-input production model, which subdues environmental preservation and reduces the margin of maneuver as a consequence of market fluctuations and possible sanitary problems. In this context, State and representative organizations of family farmers may: a) take an active role advocating for the construction of markets; or b) accept with fatalism the ongoing excluding concentration process.